Strategi Kebijakan Pemerintah dalam Menanggulangi Polusi di DLHK Kabupaten Karawang - Salfira, Elsa; Purnamasari, Hanny (Universitas Terbuka, 2024)
Strategy is essentially a careful plan for an activity to achieve a target or goal, strategy cannot be separated from the goal to be achieved without clear goals, strategy will create new problems, therefore strategy can be formulated after understanding the goal. This research aims to determine the DLHK Communication Strategy in overcoming pollution in Karawang Regency. The research method used by researchers is a descriptive research method with a qualitative approach with data collection techniques by means of observation, interviews and literature study. Meanwhile, the theory for analyzing the object of this research is the communication strategy theory put forward by Hafied Cangara consisting of research, planning, implementation, evaluation and reporting. The results of the research that has been carried out show that the communication strategy of the Karawang Regency Environment and Hygiene Service in dealing with pollution in the five dimensions of the communication strategy stage has succeeded in implementing an effective communication strategy by increasing awareness of the public and entrepreneurs to protect the surrounding environment so that air pollution does not occur.